2002
DOI: 10.1152/jn.00568.2001
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of the Precedence Effect in the Inferior Colliculus: Effect of Localization Cues

Abstract: Litovsky, R. Y. and B. Delgutte. Neural correlates of the precedence effect in the inferior colliculus: effect of localization cues. J Neurophysiol 87: 976 -994, 2002; 10.1152/jn.00568.2001. The precedence effect (PE) is an auditory phenomenon involved in suppressing the perception of echoes in reverberant environments, and is thought to facilitate accurate localization of sound sources. We investigated physiological correlates of the PE in the inferior colliculus (IC) of anesthetized cats, with a focus on dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 75 publications
6
40
0
Order By: Relevance
“…For single neurons of the IC in the cat, Yin (1994) found a median lead-lag delay of 20 ms for a 50% recovery. Similar results were obtained by Litovsky et al (2001) and Litovsky and Delgutte (2002) (lead-lag delay 32 ms). Fitzpatrick et al (1999) found increasing lead-lag delays for a 50% recovery in structures of the ascending auditory pathway (from the auditory nerve up to the cortex) in cats and rabbits.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…For single neurons of the IC in the cat, Yin (1994) found a median lead-lag delay of 20 ms for a 50% recovery. Similar results were obtained by Litovsky et al (2001) and Litovsky and Delgutte (2002) (lead-lag delay 32 ms). Fitzpatrick et al (1999) found increasing lead-lag delays for a 50% recovery in structures of the ascending auditory pathway (from the auditory nerve up to the cortex) in cats and rabbits.…”
Section: Introductionsupporting
confidence: 91%
“…Single cell studies were made in different species, e.g., in the external colliculus of the inferior colliculus of the barn owl (Keller and Takahashi, 1996), the inferior colliculus (IC) of the rabbit (Fitzpatrick et al, 1995) and the IC of the cat (Litovsky, 1998;Litovsky and Yin, 1998;Litovsky and Delgutte, 2002;Yin, 1994) and revealed that correlates of the precedence effect already exist on the level of the IC. Response rates of single neurons depend similarly on the direction of lead and lag sources and the lead-lag delay as the perceived location of the compound stimulus (lead and lag) in corresponding behavioral tasks performed by humans or cats (see, e.g., Tollin and Yin, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters for the ipsilateral and contralateral excitatory synaptic conductances, including the number of input neurons, the maximum value and the time constant of the synaptic conductance, and the delay of the input arrival, are identical to those used in Brughera et al (1996) (Kuwada and Yin 1983;Carney and Yin 1989;Loftus et al 2004). Delayed inhibitory inputs to the IC from DNLL are thought to contribute to the neural correlates of the PE (Carney and Yin 1989;Yin 1994;Fitzpatrick et al 1995;Litovsky and Yin 1998a, b;Litovsky and Delgutte 2002).…”
Section: Model Structurementioning
confidence: 99%
“…The population consisted only of SMAX units because SMAX units are thought to be more prevalent in the auditory pathway (Litovsky and Yin 1998b;Litovsky and Delgutte 2002). We used this population to simulate the results of behavioral experiments in which subjects were asked to indicate the perceived location(s) of the lead/lag target by adjusting the ITD of a pointer stimulus (Litovsky and Shinn-Cunningham 2001).…”
Section: Simulations Of Psychophysical Datamentioning
confidence: 99%